1999
DOI: 10.1093/cercor/9.5.415
|View full text |Cite
|
Sign up to set email alerts
|

Electrophysiological Studies of Human Face Perception. I: Potentials Generated in Occipitotemporal Cortex by Face and Non-face Stimuli

Abstract: This and the following two papers describe event-related potentials (ERPs) evoked by visual stimuli in 98 patients in whom electrodes were placed directly upon the cortical surface to monitor medically intractable seizures. Patients viewed pictures of faces, scrambled faces, letter-strings, number-strings, and animate and inanimate objects. This paper describes ERPs generated in striate and peristriate cortex, evoked by faces, and evoked by sinusoidal gratings, objects and letter-strings. Short-latency ERPs ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

106
593
8
3

Year Published

2002
2002
2008
2008

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 824 publications
(710 citation statements)
references
References 79 publications
106
593
8
3
Order By: Relevance
“…Our findings of a large N1 component only in the high contrast (mixed M/P) and chromatic contrast (P) conditions are consistent with the N1 emerging from ventral stream based upon P system input (Allison et al, 1999;Bentin et al, 1999;Di Russo et al, 2001;Doniger et al, 2000Doniger et al, , 2001. The present findings, however, also provide a potential cautionary note regarding the study of N1 deficits in schizophrenia.…”
Section: Discussionsupporting
confidence: 85%
“…Our findings of a large N1 component only in the high contrast (mixed M/P) and chromatic contrast (P) conditions are consistent with the N1 emerging from ventral stream based upon P system input (Allison et al, 1999;Bentin et al, 1999;Di Russo et al, 2001;Doniger et al, 2000Doniger et al, , 2001. The present findings, however, also provide a potential cautionary note regarding the study of N1 deficits in schizophrenia.…”
Section: Discussionsupporting
confidence: 85%
“…The N700 is significantly larger for faces than for other stimuli [116], suggesting local generation by face-selective modules in the occipito-temporal cortex. These findings are consistent with identity-sensitive, late, unit responses from face-selective cells in the primate temporal cortex [126].…”
Section: Erp Correlates Of Face Processing In Normal Adults and Childrenmentioning
confidence: 85%
“…Similarly, the intracranial N200, has been recorded at discrete locations over the fusiform gyrus, the inferior temporal sulcus (ITS) and the superior temporal sulcus (STS) [116]. Possibly marking the category-recognition stage, the N170 is sensitive to features usually predictive of faces, such as isolated eyes, nose or mouth [117,118], or back views of the head, or face outlines without features.…”
Section: Erp Correlates Of Face Processing In Normal Adults and Childrenmentioning
confidence: 99%
“…One previous study using intracranial ERP reported that the first distinct response in visual ventral and lateral areas appears *200 ms after stimulus onset (Allison et al 1999). In contrast, N-ERP250 and P-ERP250 in this study were observed at a latency of 250 ms, about 50 ms later than in intracranial ERP.…”
Section: Discussionmentioning
confidence: 99%